Paediatric teleradiology in low-income settings and the areas for future research in teleradiology - Savvas eAndronikou (Frontiers Media S.A., 2014)
Teleradiology is an established mechanism to overcome the lack of on-site radiologists and can benefit children in developing countries. In this 'perspective' on tele-radiology for pediatric care in underdeveloped countries, three low cost tele-radiology programs are discussed from experiences of one tele-radiologist, in relation to previous publications on this subject.Key issues discussed include mechanisms for sustainability, cost-effectiveness, resources and barriers to success. Reliance on each link of a tele-reading chain is highlighted as a constant source for concern.